2022
DOI: 10.1007/s00429-022-02576-w
|View full text |Cite
|
Sign up to set email alerts
|

Causal involvement of the left angular gyrus in higher functions as revealed by transcranial magnetic stimulation: a systematic review

Abstract: Transcranial magnetic stimulation (TMS) is a non-invasive technique that can transiently interfere with local cortical functioning, thus enabling inferences of causal left AG involvement in higher functions from experimentation with healthy participants. Here, we examine 35 studies that measure behavioural outcomes soon after or during targeting TMS to the left AG, by design and as documented by individual magnetic resonance images, in healthy adult participants. The reviewed evidence suggests a specific causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 127 publications
0
1
0
Order By: Relevance
“…Injuries to the posterior parietal cortex can result in temporary or lasting visuomotor impairments impacting hand-eye coordination and spatial navigation [22]. Furthermore, the functionality of the bilateral angular gyrus is intricately linked to the default mode network (DMN), attention, and spatial cognition [23]. Research has indicated that lesions in the left angular gyrus leading to finger agnosia will consistently result in left-right disorientation [24].…”
Section: Discussionmentioning
confidence: 99%
“…Injuries to the posterior parietal cortex can result in temporary or lasting visuomotor impairments impacting hand-eye coordination and spatial navigation [22]. Furthermore, the functionality of the bilateral angular gyrus is intricately linked to the default mode network (DMN), attention, and spatial cognition [23]. Research has indicated that lesions in the left angular gyrus leading to finger agnosia will consistently result in left-right disorientation [24].…”
Section: Discussionmentioning
confidence: 99%
“…41,42 This structure is also involved in other cognitive functions, such as memory retrieval, language (reading, writing, comprehension), numerical processing, spatial cognition, attention, and motor planning. 43 Strategic infarcts of the left angular gyrus can cause Gerstmann syndrome (acalculia, right-left disorientation, agraphia, digital agnosia) as well as disorders of language and praxis. 44,45 The role of the thalamus, which is neuroanatomically connected to the dorsolateral prefrontal cortex, extends beyond relaying sensory information to the cortex.…”
Section: Language Impairment In Cortical Vascular Dementia Due To Mul...mentioning
confidence: 99%